2014
DOI: 10.1016/j.ygyno.2013.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Metformin use and endometrial cancer survival

Abstract: Objective Impaired glucose tolerance and diabetes are risk factors for the development of uterine cancer. Although greater progression free survival among diabetic patients with ovarian and breast cancer using metformin have been reported, no studies have assessed the association of metformin use with survival in women with endometrial cancer (EC). Methods We conducted a single-institution retrospective cohort study of all patients treated for uterine cancer from January 1999 through December 2009. Demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 30 publications
0
95
1
1
Order By: Relevance
“…Two studies have demonstrated the efficacy of metformin for the treatment of endometrial cancer (43,62). In these studies, the RR of treatment with metformin was 0.49 (95% CI, 0.32-0.73; P= 0.001), with no difference in the results in meta-analysis and no heterogeneity (I 2 = 0%) (58).…”
Section: Clinical Studies Of Metformin In Gynecological Cancermentioning
confidence: 98%
“…Two studies have demonstrated the efficacy of metformin for the treatment of endometrial cancer (43,62). In these studies, the RR of treatment with metformin was 0.49 (95% CI, 0.32-0.73; P= 0.001), with no difference in the results in meta-analysis and no heterogeneity (I 2 = 0%) (58).…”
Section: Clinical Studies Of Metformin In Gynecological Cancermentioning
confidence: 98%
“…Obesity is a major risk factor for endometrial cancer; therefore, the incidence of endometrial cancer has been predicted to increase as a consequence of the obesity epidemic, which may also worsen endometrial cancer outcomes (42,43). However, the association between endometrial cancer and obesity varies according to disease histology.…”
Section: Metformin and Endometrial Cancermentioning
confidence: 99%
“…Obesity exhibits a greater association with the risk of endometrioid (type 1) endometrial cancer, than non-endometrioid (type 2) endometrial cancer (44). Data from multiple studies has indicated that the obesity-endometrial cancer association occurs as a result of the higher average circulating insulin and estradiol levels detected in obese females, and that this effect is specific to endometrioid tumors (42,45,46). There are a number of clinical studies regarding the effect of metformin on endometrial cancer outcomes.…”
Section: Metformin and Endometrial Cancermentioning
confidence: 99%
See 2 more Smart Citations